Uma visão crítica discursiva da Guerra do Contestado (1912-1916) - Oliveira, Sueli Terezinha de (2017)
This thesis understands that the social roles of João/José Maria in the Contestado War need to be revised by the Critical Analysis of Discourse and complemented by Max Weber Domination Theory. Its theme is the conflit that exists between these two characters, in the representation of history teaching texts and the oral tradition of the people. This research has its justifing due the characters João e Maria have been represented with a negative value in the History discourse and in the Teaching discourse, while in the oral tradition, they have been represented with a positive value and considered saints. This research has the general aim to contribute with the studies on the Contestado War. And the specific aims, first: to rescue the historical - political –economical view of the context of Contestado War; second: to characterize the social roles of the updated characters in the texts of Brazil History didatic books; third: to confront the values assigned by the History discourse and by the Popular Religious discourse to the same character; fourth: to analyze how the character social representations of the Contestado War, transformed the monk Giovanni, in João Maria and later in José Maria. This thesis defends that the Teaching Discourse of History is controlled by the power of the Contestado time and that João/José Maria in the people social memory have been represented by “Messianism and Sebastianism”, so that to consider them as the only character that returned to save the people of its church and political abandonment. The research is qualitative and documentary. The obtained results support this defended thesis and placing in evidence that there has been a controversial in the representations of values that have been attributed to João/José Maria, depending on the regent political regime there is a variation of these values; they indicate that according to the Typology of Domination of Weber, there are three types in the action representations practiced by José/João Maria, to know as the patriarch, the charismatic and the messianic charismatic; they also indicate that the monks João Maria e José Maria have been people contributors ,and abandoned by the church. To conclude, there is a necessity to give a continuation of these studies, so that to rescue these characters in other discourses